Estudio de la aplicación de harina de banano verde (Musa x paradisiaca) con cascara como reemplazo del maíz (Zea mays) para cerdos (sus scrofa domesticus) durante el periodo de crecimiento y engorde. - Laina Elizalde, Jonathan Isaac (2022)
In pig production, feed represents 60 to 80% of production costs. Corn is one of the most used energy sources in the pig diet, but its high price reduces the economic profits for the producer. Our objective is to study the application, analyze energy levels and compare costs of green plantain flour with peel and corn in the growth and fattening stage. The present work is a documentary research, which will be carried out by the inductive-deductive method, bibliographic documentary, information obtained from the dspace of the universities, bibliographies of academic Google, scientific articles, indexed journals and other bibliographic consultation spaces. Better daily weight gain was obtained with the addition of 30 and 40 percent of banana flour in the diet. Of the average weight for the treatments during the three periods evaluated, the one obtained by treatment 1 based on concentrate with a value of 557.36 gr. The ones that the pigs acquire a greater weight gain with banana flour, than with corn, gained an average of 2 to 3 kg/week.